A brief global agenda for advancing the study of molluscs - Sousa, Ronaldo (Frontiers in Ecology and Evolution, 2024)
Mollusca is the second largest phylum on Earth comprising more than 90,000 species. Molluscs are responsible for key functions and services in aquatic and terrestrial ecosystems. Despite their diversity and ecological and economic importance, several knowledge gaps exist concerning their basic biology. In this mini-review, I succinctly propose a new agenda for the study of molluscs for the next decade dividing it in four major topics that need urgent attention: knowledge shortfalls, monitoring at relevant spatial and temporal scales, conservation, and education and outreach. In this time of climate and biodiversity emergency, the study of molluscs and their conservation should be a priority and we cannot ignore their intrinsic and economic importance.